Fluorite‐Structured Ferroelectric and Antiferroelectric Materials: A Gateway of Miniaturized Electronic Devices. (29th April 2022) - Ali, Faizan; Ali, Tarek; Lehninger, David; Sünbül, Ayse; Viegas, Alison; Sachdeva, Ridham; Abbas, Akmal; Czernohorsky, Malte; Seidel, Konrad
Abstract: Ferroelectric (FE) and antiferroelectric (AFE) materials are used for several memory‐related and energy‐related applications. Perovskite materials (e.g.,  bulk ceramics) remain the most common materials for many applications. However, due to large deposition thickness, these materials are not appropriate for future miniaturized devices. In 2011, FE and AFE properties were reported in Si‐doped HfO2 thin films. HfO2 ‐based FE and AFE materials have several advantages over conventional materials, such as ultrathin deposition thickness (in range of nanometers), compatibility with existing Si semiconductor technology, and suitability for the integration within 3‐D nanostructures. Therefore, fluorite‐structured materials can be appropriate for miniaturized devices. These fluorite‐structured materials are extensively studied for memory and energy‐related applications. The first review on this topic was published after four years of discovering the FE and AFE properties in these materials. From the past decade, a lot of research has been reported about the detailed mechanism and application of these materials. This review insightfully discusses the progress in the research of fluorite‐structured materials and critically discusses some potential applications. Here some challenges are also discussed, new knowledge is extracted, and promising future research directions of these materials are suggested. Abstract : Fluorite‐structured ferroelectric and antiferroelectric materials can be appropriate for future miniaturized devices. These materials can be used for energy‐related applications (energy harvesting, energy storage, solid‐state cooling, thermal imaging), and memory applications (ferroelectric memories and transistors). This review summarizes the current status of research in the emerging fluorite‐structured ferroelectrics and antiferroelectrics with respect to their applications.